Effect of HPLC Separated Flavonoids Extracted from Centraurea Cineraria to Some Species of Bacterial Pathogenicity - Zeinab Hashim Mohammed (Journal of Global Pharma Technology, 2018)
The research included the separation and determination of flavonoids from the extract of Centraurea Cineraria gray using the high-performance liquid chromatography technique. Cirsilineol, Jaceosidin, Melitensin, Apigenin and Prunasin were found to be identical to the standard compounds used in chromatography analysis. The flavonoids found in the extract were detected using qualitative chemical analyzes. The effect of the gray catheter extract containing the flavonoids mentioned above was studied in five bacterial species (Escherichia coli, Streptococcus pneumonia, Klebsiellaspp Staphylococcus aureus, Pseudomonas aeruginosa) using Agar well diffusion method and then added concentrations (100,75,50,25 mg / Ml of the extract and the measuring sieve. The transparent zone of the bacterial growth inhibitor showed a concentration of 100 mg / ml inhibitory capacity with a zone of 17 mm inhibition for Klebsella.